221 BEFRIENDING SERVICES ARE ASSOCIATED WITH LESS DECLINE IN HEALTH-RELATED QUALITY OF LIFE, BUT NOT COGNITIVE FUNCTION, OVER TIME. (25th October 2022) - Power, JM; Hannigan, C; Scharf, T; Moynihan, S; Walsh, C; Johnson, N; Lawlor, B; Holton, E; Kee, F
Abstract: Background: Befriending services are commonly deployed in the support of older people living alone, but lack an established evidence base, particularly in relation to their association with health outcomes. Methods: To explore the potentially therapeutic impact of befriending on Health-Related Quality-of-Life (HR-QoL) and cognitive function, we used a single case experimental design. Data were collected from 85 new users of ALONE's befriending service between 2019 and 2021 in an AB multiple baseline design. Generalised additive modelling was then used to assess trajectories of HR-QoL and cognitive function (semantic fluency) over the course of six months, and its association with the onset of the befriending service intervention Results: The befriending service was associated with less decline over time in HR-QoL, and with a mitigated impact of loneliness on HR-QoL too. No such effects were observed for cognitive function as an outcome, which did not change over time. Conclusion: Befriending may exert a positive effect on health-related quality of life, and reduce the negative impact that loneliness has on this outcome.